Media Matter - Holger Pötzsch (tripleC: Communication, Capitalism & Critique)
The present contribution maps materialist advances in media studies. Based on the assumption that matter and materiality constitute significant aspects of communication processes and practices, I introduce four fields of inquiry - technology, political economy, ecology, and the body - and argue that these perspectives enable a more comprehensive understanding of the implications of contemporary technologically afforded forms of interaction. The article shows how each perspective can balance apologetic and apocalyptic approaches to the impact of in particular digital technologies, before it demonstrates the applicability of an integrated framework with reference to the techno-politics of NSA surveillance and the counter-practices of WikiLeaks.